2008
DOI: 10.1583/08-2359.1
|View full text |Cite
|
Sign up to set email alerts
|

Acute and Long-term Outcome of Endovascular Therapy for Aortoiliac Occlusive Lesions Stratified According to the TASC Classification:A Single-Center Experience

Abstract: In experienced hands, endovascular therapy of aortoiliac lesions can be successfully performed with sustained long-term outcome independent of the TASC II classification, even in class D lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
58
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(67 citation statements)
references
References 25 publications
7
58
0
2
Order By: Relevance
“…Baseline characteristics of the patients with technical success according to the need for TLR combined outflow lesions are independent predictors of loss of primary patency. [15][16][17][18] In the present study, we found that small EIA diameter was also an important determinant of TLR. Similarly, Soga et al reported that reference vessel diameter <8.0 mm measured by angiography during the procedure was an independent predictor of restenosis.…”
Section: Supplementary Filessupporting
confidence: 62%
“…Baseline characteristics of the patients with technical success according to the need for TLR combined outflow lesions are independent predictors of loss of primary patency. [15][16][17][18] In the present study, we found that small EIA diameter was also an important determinant of TLR. Similarly, Soga et al reported that reference vessel diameter <8.0 mm measured by angiography during the procedure was an independent predictor of restenosis.…”
Section: Supplementary Filessupporting
confidence: 62%
“…However, thanks to modern endovascular equipment and techniques, the successful treatment of a growing number of TASC II D lesions is now possible (13), and this trend associated with our favorable results suggests that CFA stenosis may reasonably be treated with an endovascular approach first. Study limitations.…”
Section: Discussionmentioning
confidence: 86%
“…Grâce à des progrès considérables dans le matériel, dans les techniques de revascularisation et dans l'habileté interventionnelle des opérateurs, le traitement endovasculaire représente une option intéres-sante chez un nombre considérable de patients souffrant d'insuffisance artérielle des membres inférieurs. Les avantages principaux d'une approche percutanée par rapport à la chirurgie sont un taux de complication cardiovasculaire faible (0,5-4 % vs 10-15 % pour la chirurgie, avec un taux de mortalité d'environ 2-3 %) [2], un taux de succès technique immédiat qui approche les 90 %, même pour des lésions complexes, [2,4] et des taux de perméabilité satisfaisants, permettant, soit l'amélioration d'une claudication, soit « de passer un cap » pour favoriser la guérison d'un trouble trophique.…”
Section: Techniques Et Matériels Endovasculairesunclassified
“…Ce n'est que récemment, qu'il a pu être démontré que même les lésions TASC II D peuvent également être abordées de façon percutanée, avec un taux de succès technique immédiat élevé et un taux de perméabilité secondaire à deux ans acceptable [4][5][6].…”
unclassified